Personnel Awareness on Cultural Data Management in Municipalities: The Sample of Ankara Metropolitan Municipality - Gezer, Haydar; Öztemiz, Semanur (Information World, 2025)
This study aimed to reveal personnel awareness of cultural data management processes and to examine institutional performance evaluations in municipalities, using a sample from the Ankara Metropolitan Municipality. In this research, a quantitative method was used, and data were collected through a questionnaire with four sections. The findings indicate that the cultural data management awareness among personnel is at a level that can be improved. Most of the respondents evaluated the institution’s performance regarding cultural data management as moderately adequate. The study found a statistically significant relationship between awareness of cultural data management and perceived institutional performance. The results also showed that personnel awareness on cultural data management do not differ by age, gender, educational status, or title. This study is expected to promote further research on cultural data management in local governments and to contribute to the existing literature on the subject.
Keywords: Personnel awareness; institutional performance; cultural data; cultural data management; municipalities; Ankara; Türkiye